Microabrasion of Cast Metal MarginsÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬ÂA Warning - Michael A. Mansueto, DDS, MS;1 Ronald G. Verrett, DDS, MS;1 (Journal of Prosthodontics, 2007)
Plastic test patterns were milled to simulate casting margins and were cast in a variety of dental alloys.